Anthocyanins from rubus fruticosus l. And morus nigra l. applied as food colorants: a natural alternative - Vega, Erika N. (2018)
Given the importance of colour in the general acceptance or rejection of a product, the use of colorants is a widespread practice, particularly in the food industry. At the same time, with the increasing consumers’ awareness of the health effects that some artificial colorants can exert, there is a growing tendency to prioritize foodstuffs containing natural additives. In this work, Morus nigra L. and Rubus fruticosus L. fruit juices were characterized in terms of anthocyanins, organic acids, free sugars, and tocopherols, as also regarding their bioactive properties. Given their richness in anthocyanins, this study also aimed to prepare different solid colouring formulations by the spray-drying technique, using as stabilizers maltodextrin and arabic gum. Six free sugars and two organic acids were detected in the fruit juices, as well as the four tocopherol isoforms. Two cyanidin derivatives were found in M. nigra (cyanidin-3-O-glucoside and cyanidin-O-rhamnoside) and other four in R. fruticosus (cyanidin-O-hexoside, cyanidin-3-O-glucoside, cyanidin-O-pentoside, and cyanidin-3-O-dioxaloilglucoside). The developed colouring formulations revealed a good stability over time, in terms of anthocyanin concentration and colour parameters, and revealed to be safe for consumption, either concerning their low microbial load and lack of cytotoxicity. Thus, they represent a promising natural alternative to the massively used artificial colorants.